Analysis of the Working System of a Carcinogenic Substance Neutralization Device (Smoke/Gas) in Enclosed Space Using an MQ2 Sensor Based on Arduino Uno - Nuraprilyani Pasaribu; Beni Satria; Ahmad Dani (INFOKUM, 2025)
Air pollution in enclosed spaces, particularly from carcinogenic substances such as smoke and hazardous gases, poses significant health risks. Effective detection and neutralization of these harmful compounds are crucial to ensuring indoor air quality and human safety. This study analysed the working system of a carcinogenic substance neutralization device that utilizes an MQ2 gas sensor and Arduino Uno for real-time monitoring and control. The system is designed to detect the presence of carbon monoxide (CO), liquefied petroleum gas (LPG), smoke, and other harmful gases using the MQ2 sensor. When the sensor detects a gas concentration exceeding a predefined threshold, the Arduino Uno microcontroller triggers an exhaust fan or an air purification mechanism to neutralize the pollutants. The system also features a real-time display and an alarm to alert users of hazardous gas levels. The experimental results indicate that the MQ2 sensor effectively detects gas concentrations with a fast response time. The Arduino-based control system efficiently activates the neutralization process, improving air quality in enclosed spaces. The integration of this system with smart monitoring devices can enhance air pollution management in industrial, residential, and commercial environments. This paper contributes to the development of low-cost, automated air purification systems for enclosed spaces, with potential applications in health safety, environmental protection, and industrial settings. Future research may focus on integrating IoT-based remote monitoring and advanced filtration technologies to enhance the system’s efficiency and adaptability.